Utility of a patient similarity-based digital tool for risk communication to patients with type 2 diabetes mellitus: perspectives from primary care physicians in ambulatory care. - Ruiheng Ong; Chirk Jenn Ng; Kalaipriya Gunasekaran; Hang Liu; Wynne Hsu; Mong Li Lee; Ngiap Chuan Tan (PLoS ONE)
Background Inaccurate risk perceptions of diabetes complications are responsible for the inertia among patients to engage in protective health behaviours. One potential approach to changing risk perceptions is to use social comparison of their diabetes to other people of similar clinicodemographic profiles. Objectives This study examined the perspectives of primary care physicians (PCPs) in ambulatory care on the utility of a patient similarity-based digital tool for risk communication to patients with type 2 diabetes mellitus (T2DM). Methods A qualitative study design using direct observation and in-depth interviews was conducted on 11 PCP participants. Participants had at least 6 months of clinical experience in ambulatory primary care. Participants went through three hypothetical case scenarios using the digital tool under direct observation and shared their perspectives on its utility during an in-depth interview. Data were coded and analysed using thematic analysis. Results PCPs perceived the digital tool to be useful in educating patients with newly diagnosed or uncontrolled T2DM and to motivate them to achieve better glycated haemoglobin (HBA1c) levels. Patients who do not practise social comparison would refrain from HBA1c comparison and prefer to know the absolute state of their diabetes. PCPs were also concerned about patients' potential for false reassurance or negative reactions instead of correctly understanding the risk message intended for them. Conclusion The patient similarity-based digital tool requires further work to support PCPs in risk communication to patients with T2DM. Usage should be targeted at patient subgroups with newly diagnosed or uncontrolled T2DM and who practise social comparison. Strategies to maximise benefit include identifying patients who practise social comparison and training PCPs to be adept at framing and communicating risk information in a person-centric manner to mitigate the possibility of false reassurance or negative reactions from their patients.